Madame Tussaud : a life in wax - Berridge, Kate. (New York : W. Morrow, 2006)
Chronicles the life of the real Madame Tussaud, discussingher childhood, the reversal of fortune that changed her life, the wax museums she founded, and other related topics.
Published under the title: Waxing mythical. London : J. Murray, 2006.
Includes bibliographical references (p. 327-336) and index.
Library Journal.
Adult
Keywords: Tussaud, Marie, -- 1761-1850.; Tussaud, Marie, -- 1761-1850.; Wax modellers -- France -- Biography; Wax modellers -- Biography; France -- History -- Revolution, 1789-1799.; France -- History -- 1789-1799, Revolution